Tissue temperature, flux and oxygen of sacral and trochanteric area under pressure of healthy subjects: A quasi-experimental study. - Lupiáñez-Pérez, Inmaculada; Gómez-González, Alberto José; Marfil Gómez, Raquel M.; Morales-Asencio, José Miguel; García-Mayor, Silvia; León-Campos, Álvaro; Kaknani-Uttumchandani, Shakira; Moya-Suárez, Ana Belén; Aranda Gallardo, Marta; Morilla-Herrera, Juan Carlos (Elsevier, 2021)
Aim: To evaluate the changes that take place in the perfusion, oxygenation and local temperature of the skin of the sacrum and trochanter when subjected to direct pressure for 2 h. Methods: Quasi-experimental study in the preclinical phase with healthy subjects acting as their own controls (intrasubject control). The outcome variables were measured with a laser Doppler system (local temperature and oxygenation) and by near-infrared spectroscopy (perfusion). The pressure exerted was measured with a capacitive pressure sensor. No more than one week elapsed between the sacrum and trochanter measurements. Results: The study sample consisted of 18 persons. The comparative analysis of the fluctuations in the parameters measured on the skin of the trochanters and sacrum, according to the time elapsed, revealed a statistically significant increase in temperature and in the pressure exerted. On the other hand, the changes in capillary blood flow and in SaO2 were not statistically significant. Conclusion: Our study results show that changes found in terms of temperature and pressure should be taking into account when planning personalised repositioning to patients according to biomechanical and biological situations that vary between anatomical areas. In future research, the changes reported could be evaluated in patients with risk factors for the development of pressure ulcers, thus facilitating the introduction of more personalised planning in the care and prevention of these injuries.
https://openpolicyfinder.jisc.ac.uk/id/publication/14144
Keywords: Enfermería; Ulceras por presión; Velocimetría láser Doppler sanguínea; Nursing pressure ulcer blood